2009
DOI: 10.1038/onc.2009.293
|View full text |Cite
|
Sign up to set email alerts
|

A novel pro-apoptotic function of RACK1: suppression of Src activity in the intrinsic and Akt pathways

Abstract: Earlier we showed that RACK1 regulates growth of human colon cells by suppressing Src activity at G 1 and mitotic checkpoints. Here, we show that RACK1 also induces apoptosis of the cells, partly by inhibiting Src. In the intrinsic pathway, RACK1 inhibits expression of anti-apoptotic Bcl-2 and Bcl-X L , induces expression of proapoptotic Bim, targets Bim and Bax to the mitochondria, induces oligomerization of Bax (which requires Bim and inhibition of Src), depolarizes mitochondria membranes, releases cytochrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 53 publications
3
50
0
Order By: Relevance
“…We chose HT-29 cells for these studies because we showed that Src-specific activity is elevated in the cells and can be suppressed by overexpression of Rack1 or by incubating the cells with cell-permeable peptides that enhance Rack1's interaction with Src (Mamidipudi et al, 2007). We also showed that Rack1 regulates the growth of these cells by suppressing Src activity at G 1 and mitotic checkpoints, and in the intrinsic apoptotic and Akt cell survival pathways (Mamidipudi et al, 2007;Mamidipudi and Cartwright, 2009). Others showed that increased Src activity in HT-29 cells disrupts E-cadherin adhesion as a result of aberrant tyrosine phosphorylation of the E-cadherin/catenin complex (Skoudy et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose HT-29 cells for these studies because we showed that Src-specific activity is elevated in the cells and can be suppressed by overexpression of Rack1 or by incubating the cells with cell-permeable peptides that enhance Rack1's interaction with Src (Mamidipudi et al, 2007). We also showed that Rack1 regulates the growth of these cells by suppressing Src activity at G 1 and mitotic checkpoints, and in the intrinsic apoptotic and Akt cell survival pathways (Mamidipudi et al, 2007;Mamidipudi and Cartwright, 2009). Others showed that increased Src activity in HT-29 cells disrupts E-cadherin adhesion as a result of aberrant tyrosine phosphorylation of the E-cadherin/catenin complex (Skoudy et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Previously we identified Rack1 as a novel substrate and inhibitor of Src (Chang et al, 1998(Chang et al, , 2001(Chang et al, , 2002. We showed that Rack1 regulates the growth of cells by inhibiting Src activity at G 1 and mitotic cell-cycle checkpoints and cell survival pathways (Mamidipudi et al, 2004(Mamidipudi et al, , 2007Mamidipudi and Cartwright, 2009). Rack1 also functions in protein kinase-C, insulin growth factor receptor and integrin signaling pathways (Schechtman and Mochly-Rosen, 2001;McCahill et al, 2002;Cox et al, 2003;Kiely et al, 2005;Doan and Huttenlocher, 2007;Vomastek et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our data support the role of RACK1 as an antiapoptotic protein in cells. Several groups reported that RACK1 can promote apoptosis (28,29). Controversially, RACK1 has been reported to suppress apoptosis in multiple types of cells, such as PC-12 cells (30), W7.2 T cells (47,48), and HeLa cells (49).…”
Section: Discussionmentioning
confidence: 99%
“…
We have read with great interest the recent article by Mamidipudi and Cartwright (2009), in which the authors showed that RACK1 induced apoptosis of human colon cells by inhibiting the expression of antiapoptotic pathways and Src activity, thus leading to death of colon cancer cells.We have recently conducted an analysis of RACK1 messenger RNA (mRNA) expression in 127 human breast cancer and 33 non-cancerous breast tissue specimens. The study was carried out using reverse transcriptase-polymerase chain reaction following RNA extraction from frozen samples.
…”
mentioning
confidence: 94%
“…We have read with great interest the recent article by Mamidipudi and Cartwright (2009), in which the authors showed that RACK1 induced apoptosis of human colon cells by inhibiting the expression of antiapoptotic pathways and Src activity, thus leading to death of colon cancer cells.…”
mentioning
confidence: 94%